KINERJA KOMITE SEKOLAH DALAM RANGKA MENINGKATKAN MUTU PENDIDIKAN DI SDIT AL-AZHAR 2 KECAMATAN SEKUPANG KOTA BATAM PROVINSI KEPULAUAN RIAU - jurnalmap map; Anita ÔÇì; Indra Prasetyo; Sri Mulyani (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2019)
ABSTRACT The aim of this research is to know and analyze the role of cominte school in order to improve the quality of education in SDIT Al-Azhar 2 Batam as an educational institution that has formed a school committee. The school committee's performance is 1). As an Advisory Agency, (2) supporting agency, (3) Controlling Agency, and (4) Mediator agency. The results of the study and data analysis explained that the performance of the school committee of Al-Azhar 2 Batam SDIT in order to improve the quality of education has not been seen to be optimal due to communication that has not gone well between the school and the school committee as work partners. The efforts made to maintain conditions become more is to improve communication, coordination, socialization by creating new agendas for committees and school parties, and involving school citizens namely guardians to play an active role in supporting educational activities in SDIT Al-Azhar 2 Batam Sekupang District, Batam City Riau Islands province. Keywords: School committee, role and quality